DATABASE MANIPULATIONS AS RELATION-TYPE OPERATIONS - Mezník, Ivan (European Scientific Journal, ESJ, 2015)
The paper points to highly useful symbiosis of manipulations in databases and operation on relation-type mathematical structures. The common context of n-ary relation tools and database structures means is discussed and the correspondence between n-ary relation operations and standard database constructions is examined. Also some relevant mathematical problems are pointed out. Relationships among elements of a number of sets often arise in real-life events and lead to investigation of important properties of discrete algebraic structures. For instance, there is a relationship among the name of the passenger, the name of the aircraft carrier, flight number, departure point, destination, departure time, and arrival time. Such relationships may be expressed in terms of n-ary relations.